The Effect Of Gender Diversity On Company Value With Company Performance As An Intervening Variable In Service Sector In Indonesia Stock Exchange - Khuldia, Khuldia; laba, Abd. Rakhman; Pakki, Erlina (STIE AMKOP, 2023)
Current developments and the economy are developing very quickly, thus requiring economic actors to be able to adapt to change. Companies that can compete well will not experience failure or bankruptcy but will continue to grow to get high scores. This study aims to examine the effect of gender diversity on the board on firm performance with firm performance as an intervening variable. This type of research uses quantitative research with an associative approach. The samples in this study were 110 samples. The data analysis technique in this study used Structural Equation Modeling (SEM) with the help of SmartPLS. The results of this study indicate that gender diversity has no significant effect on firm performance, gender diversity has a significant effect on firm value, firm performance has no significant effect on firm value, and gender diversity has no significant effect on firm value through firm performance in service companies. on the Stock Exchange. Key Words: Gender Diversity, Company Value, Firm Performance